The Metabolic Syndrome in Hispanics - The Role of Inflammation - Pablo I Altieri; Jose Marcial; Hector L Banchs; Nelson Escobales; María Crespo (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2015)
We report clinical and molecular mechanisms relating the pro-inflammatory and anti-inflammatory process in the development of the components of the metabolic syndrome, emphasizing the cardiovascular problems developed in these groups of patients, especially the Hispanic population. Namely, the incidence, component characteristics and complications of the metabolic syndrome in island Puerto Ricans are described and evidence is presented supporting the fact that the metabolic syndrome may be milder in Puerto Rico than in the mainland United States because it is characterized by less aggressive coronary artery disease and a relatively normal lipid profile. Moreover, data supports the fact that increased serum cholesterol levels produce less myocardial infarctions in Puerto Rico than in mainland Hispanics and Caucasians. In addition, the incidence of ventricular tachycardia, a complication caused by remodeling and ischemia of the heart, may be lower in Puerto Rico than in the United States, although the prevalence of the metabolic syndrome is higher in the island.